Effect of Mentoring on Military Personnel Retention - Aman, Shewakena (Edelweiss Applied Science and Technology, 2018)
Retention of human capital is an asset to any organization and as a result, mentoring and retention has become an issue of importance for any organization. This study, therefore, analyzed the effect of mentoring on military personnel retention in Ethiopian military a cademies. Methodologically, the research approach is quantitative and the design was descriptive and explanatory type of research, where the population of the study is the protégés of military academies in Ethiopia. The sampling method is probability and specifically stratified random sampling. The data were collected using structured questionnaires. The researcher used both descriptive and inferential statistics. The result of person correlation revealed that mentoring has positive and significant relationship with personnel retention in military academies. Furthermore, the results of regression analysis indicated that mentoring has positive and significant effect on personnel retention in the studied academies. It was found that psychological mentoring has higher effect on military personnel retention than career mentoring and role modeling. Findings of this study shows that providing mentoring for military personnel is positively and significantly related to higher psychological readiness, career development, and personnel retention. Military academies are better to emphasize on psychological mentoring to enhance the retention of military personnel.